Outdoor Theatrical Shows in the Remarkable Landscapes of the Chinese Mountains, Between Reinvention of a Tradition and Development of Tourism: the Example of the ‘Tianmen Fox Fairy Show’ at Zhangjiajie - Wei Xiang; Philippe Bachimon; Pierre Dérioz (Revue de Géographie Alpine)
Using a case study (Zhangjiajie), this article discusses the status accorded to outdoor theatrical shows in the remarkable mountainous landscapes of China. This type of performance has become very widespread in the country since 2004. In the form of a sound-and-light musical drama, it adopts a mythified and very formalized approach that uses and embraces the marvellous landscape and attempts to link spectacular technical effects to a stereotypical artistic approach. As an object of tourist consumption, it leads us to question the notion of ‘culture’ to which it attaches itself, emphasizing the disconnect it presents in terms of Western norms. A kitsch ‘mass’ show, it constitutes both a commercial reality of a new China and the postmodern modality of a cultural approach inherited from an official socialist discourse that is today legitimizing its actions by attaching itself to tradition.